Impact of nanocarrier aggregation on EPR-mediated tumor targeting - Surya Teja, S. P.; Damodharan, N.; Tamilanban, T.; Subramaniyan, Vetriselvan; Chitra, V.; Chinni, Suresh V.; Wong, Ling Shing; Fuloria, Neeraj Kumar; Sekar, Mahendran; Fuloria, Shivkanya; Ramachawolran, Gobinath; Selvaraj, Siddharthan (Frontiers in Bioengineering and Biotechnology, 2023)
The aim of this study was to investigate the influence of excipients on retaining the particle size of methotrexate (MTX) loaded chitosan nanocarriers (CsNP) during lyophilization, which relates to the ability to enlarge the particle size and target specific areas. The nanocarriers were prepared using the ionic gelation technique with tripolyphosphate as a crosslinker. Three lyophilized formulations were used: nanosuspension without Lyoprotectant (NF), with mannitol (NFM), and with sucrose (NFS). The lyophilized powder intended for injection (PI) was examined to assess changes in particle size, product integrity, and comparative biodistribution studies to evaluate targeting ability. After lyophilization, NFS was excluded from in-vivo studies due to the product melt-back phenomenon. The particle size of the NF lyophile significantly increased from 176nm to 261nm. In contrast, NFM restricted the nanocarrier size to 194nm and exhibited excellent cake properties. FTIR, XRD, and SEM analysis revealed the transformation of mannitol into a stable β, δ polymorphic form.Biodistribution studies showed that the nanocarriers significantly increased MTX accumulation in tumor tissue (NF=2.04±0.27; NFM=2.73±0.19) compared to the marketed PI (1.45±0.25µg), but this effect was highly dependent on the particle size. Incorporating mannitol yielded positive results in restricting particle size and favoring successful tumor targeting. This study demonstrates the potential of chitosan nanocarriers as promising candidates for targeted tumor drug delivery.